COVID-19: travel intention and restoring travelers' confidence / Christy Bidder ... [et al.] - Bidder, Christy Bidder; Aidi, Muhammad Zulhazmi; Hong, Leanne Marian; Fatt, Boyd Sun; Kibat, Silverina Anabelle; Mogindol, Spencer Hedley; Daniel, Shareen Dina; Jailani, Sylviana Imelda (Universiti Teknologi Mara Cawangan Pulau Pinang, 2021)
The study examined the non-economic impact of COVID-19 on tourist behaviour, specifically from the perspective of travel intention and restoration of travellers' confidence in travelling again during and post-pandemic. Data were collected with an online questionnaire using the snowball sampling method. A total of 150 respondents completed the questionnaire. A descriptive statistical test was used to analyse the data collected. Research findings reveal a pessimistic outlook on travel intention. Individuals may feel sceptical and wait six months or longer before engaging in tourism activities again, even after the pandemic is brought under control. Most individuals may only be motivated to travel again when the COVID-19 vaccine becomes available. It was also discovered that when it comes to the restoration of travellers' confidence, measures that can be seen, calculated, or proved may work best, such as face mask-wearing, social distancing, hand sanitising as well as disinfection and sterilisation. There may also be a perception difference between what service providers perceive as critical and what travellers perceive as indispensable for the restoration of travellers' confidence. It is the latter's perception that will and should matter the most. Research findings are based on travellers' perception, hence the importance of expanding research scope to examine actual travel behaviour when COVID-19 is over and tourism bounces back to "normal."